Bronchial responsiveness to histamine: relationship to diurnal variation of peak flow rate, improvement after bronchodilator, and airway calibre. Issue 6 (June 1982) - Ryan, G; Latimer, KM; Dolovich, J; Hargreave, FE
Abstract : Features of asthma include increases in both bronchial responsiveness and variability of airflow rates. We examined the relationship between bronchial responsiveness to histamine and the variation of peak expiratory flow rate (PFR) during the day and in response to salbutamol (200 μg), and the initial FEV1 at the time of the histamine test and FEV1 response to salbutamol. Bronchial responsiveness to histamine was expressed as the provocation concentration causing a fall in FEV1 of 20% (PC20 ). PC20 ranged between 13·9 and 130 mg/ml in nonasthmatic subjects, between 10·5 and 59·9 mg/ml in five asymptomatic asthmatics, and between 0·03 and 20·8 mg/ml in 27 asthmatics with symptoms controlled by medication. The lower the PC20 (the greater the bronchial responsiveness) the lower the morning PFR (r = 0·79), the greater the increase in PFR after salbutamol (morning r = −0·75, evening r = −0·80), and the greater the difference between the highest and lowest PFR each day (r = −0·81). Measurements of PFR were abnormal, compared with those in nonasthmatic subjects, in all subjects with a PC20 less than 2 mg/ml—that is, moderate or severe increase in nonspecific bronchial responsiveness—and in none with a PC20 greater than 21 mg/ml—that is, normal responsiveness; five of nine asthmatics with controlled symptoms had abnormal PFR measurements when PC20 was between 2 and 21 mg/ml—that is, mild hyperresponsiveness. In contrast, FEV1 at the time of the histamine test was greater than 80% predicted in all subjects with a PC20 greater than 2 mg/ml and was not less than this in 10 of 18 subjects with a PC20 less than 2 mg/ml. When improvement in FEV1 was 20% or more after salbutamol, the PC20 was usually moderately or severely increased (less than 0·4 mg/ml). The results identify a close relationship between nonspecific bronchial responsiveness to histamine and the variability in flow rates which occurs spontaneously and after bronchodilator. In addition, they raise the possibility that increased airflow obstruction in asthma may be a consequence of increased responsiveness.